2018
DOI: 10.1111/jeb.13349
|View full text |Cite
|
Sign up to set email alerts
|

Major histocompatibility complex variation and blood parasites in resident and migratory populations of the common yellowthroat

Abstract: Genes of the major histocompatibility complex (MHC) are a critical part of the adaptive immune response, and the most polymorphic genes in the vertebrate genome, especially in passerine birds. This diversity is thought to be influenced by exposure to pathogens which can vary in relation to numerous factors. Migratory behaviour may be a particularly important trait to consider because migratory birds are exposed to a greater number of different pathogens and parasites at both breeding (i.e. temperate) and overw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
18
0
1

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(19 citation statements)
references
References 125 publications
0
18
0
1
Order By: Relevance
“…While this hypothesis needs further testing, we also have to acknowledge that the link between migration and the mechanisms shaping genetic variation at the two MHC classes may differ between species. For example, a recent study by Whittingham et al. (2018) revealed higher MHC class I, but not class II, diversity in migratory than resident populations of the common yellowthroat.…”
Section: Discussionmentioning
confidence: 99%
“…While this hypothesis needs further testing, we also have to acknowledge that the link between migration and the mechanisms shaping genetic variation at the two MHC classes may differ between species. For example, a recent study by Whittingham et al. (2018) revealed higher MHC class I, but not class II, diversity in migratory than resident populations of the common yellowthroat.…”
Section: Discussionmentioning
confidence: 99%
“…The MHC exhibits extraordinary evolutionary dynamics with rapid expansions and contractions of MHC gene copy number, and substantial variation in MHC sequence and haplotype structure (Kelley, Walter, & Trowsdale, 2005;Minias et al, 2018;Masatoshi Nei & Rooney, 2005;O'Connor et al, 2016;Ohta, 1991;Spurgin et al, 2011). Thus, previous studies have reported considerable variation in the number of different MHC alleles between individuals within species, suggesting that MHC gene copy number variation may be a common trait, at least among birds (Biedrzycka, O'Connor, et al, 2017;Gaigher et al, 2016;Roved et al, 2018;Stervander, Dierickx, Thorley, Brooke, & Westerdahl, 2020;Whittingham, Dunn, Freeman-Gallant, Taff, & Johnson, 2018). Our analyses of MHC-I haplotypes confirmed previous indications of substantial MHC-I gene copy number variation in the great reed warbler (O'Connor et al, 2016;Roved et al, 2018), with a minimum of 4 and a maximum of 21 different MHC-I alleles per haplotype (Fig.…”
Section: Discussionmentioning
confidence: 99%
“…For instance, increased mean MHC diversity has been associated with migratory behaviour and female promiscuity, two traits that may increase exposure and/or reduce immune response to parasites (Gohli et al, 2013;Minias, Pikus, Whittingham, & Dunn, 2019;Whittingham, Dunn, Freeman-Gallant, Taff, & Johnson, 2018;Winternitz et al, 2013). In contrast, studies investigating interindividual variation in the fitness consequences of MHC diversity within a population are scarce, although there is extensive evidence for interindividual variations in these potential selective pressures (i.e., exposure to parasites, immune response strength or susceptibility to autoimmunity).…”
mentioning
confidence: 99%